(untitled) (Altre Modernità, 2019)
Salón de belleza (Mario Bellatin, 1994) poses a series of metamorphoses related to space and identity: the transition from health to illness, and the transformation of the beauty salon into "moridero". The story postulates a nomadic, unstable and migrant subjectivity that is defined in terms of becoming rather than being. Now, the irruption of a terminal illness involves the expulsion of sick people from public hospitals, insofar as they are not recoverable for the production chain. Bellatin’s novel constructs a double and contradictory scene to expose the effects of hierarchy and categorization of logos on life, and reproduces the exclusions of the biopolitical power that determines which lives matter and which do not. At the same time, the dynamics of a fundamentally metamorphic microcosm cancel the immobility of frontiers and destabilize rigid classifications